QASHQADARYO VILOYATIDA TURKISTON TERMITI (ANACANTHOTERMES TURKESTANICUS JACOBS) FAUNASINING MONITORINGI - Ruziboyeva M.R., Ruziboyeva M.R. (Actual problems and prospects of the study of the fauna, 2024)
According to the monitoring results of Turkestan termite - Anacanthotermes turkestanicus spread in Kashkadarya region, it was found to be found in 2558 buildings and structures and 5 state institutions. According to the indicators of the analysis, Guzor, Koson, Chirakchi and Karshi districts of the region were dominant in terms of damage by termites compared to other regions. There are more than 1000 nests of termites in open biotope areas of the region.